2016
DOI: 10.21614/jtmr-21-2-85
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Optimal Experimental Model for Immunological Studies in VCA: Vascularized Composite Allotransplants Based on Femoral Vessels in Rats

Abstract: Vascularized composite allotransplantation (VCA) has become a recent therapeutic entity in reconstructive surgery. Long term immunosuppressive therapy ensures graft survival, although, with a risk of serious side effects. Further progress in this field depends on better understanding of basic immunology of composite tissue grafts with the dynamics of rejection and possibilities to induce donor specific-tolerance. Without a vast clinical experience, a possibility for achieving those goals is intensive study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Study characteristics are shown in ►Tables 2 and 3. [16][17][18][19][20][21][22] The majority of the animal studies were performed to evaluate the immunosuppression regimen and feasibility of AW-VCA. The anatomic landmarks were similar among studies; superiorly, the xiphoid process and costal margin, laterally the anterior axillary lines, and inferiorly the inguinal ligament (0-1 cm) below and the pubic tubercle.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Study characteristics are shown in ►Tables 2 and 3. [16][17][18][19][20][21][22] The majority of the animal studies were performed to evaluate the immunosuppression regimen and feasibility of AW-VCA. The anatomic landmarks were similar among studies; superiorly, the xiphoid process and costal margin, laterally the anterior axillary lines, and inferiorly the inguinal ligament (0-1 cm) below and the pubic tubercle.…”
Section: Animal Studiesmentioning
confidence: 99%